Expression of D7 and D7-related proteins in the salivary glands of the human malaria mosquito Anopheles stephensi - Suwan N. (2014)
Full-length cDNA clones encoding D7 (AnsD7) and D7-related (AnsD7r1) secreted salivary gland proteins were isolated from Anopheles stephensi. Corresponding proteins were separated by SDS-PAGE and analysed by N-terminal sequencing, which also identified a second D7-related protein (AnsD7r2). AnsD7 encodes a protein of 37 kDa, AnsD7r1 of 18 kDa, and AnsD7r2 of 16 kDa. Polyclonal antibodies against recombinant AnsD7 showed immunological cross-reactivity with the D7-related proteins, and alignment demonstrated sequence similarity between the C-terminal region of AnsD7 and the D7-related proteins. AnsD7, AnsD7r1 and AnsD7r2 were major female-specific salivary gland proteins, and Western blotting, immunohistochemistry and immunogold labelling demonstrated expression was predominantly in the secretory cavities of the distal-lateral and median lobes. Expression and localization of D7 and D7-related proteins was similar in Plasmodium berghei-infected and uninfected mosquitoes.